Development and storage stability of spray dried ubi (Dioscorea alata Linn.) anthocyanin pigment as food colorant - Ramos, Aida
Red and violet food colorant were obtained by hot water extraction of ubi and then spray drying of the concentrated extract. Maltodextrin was used as a carrier agent and was added to obtain slurries containing 1%, 2%, and 3% maltodextrin. The product with the optimum level of added maltodextrin was compared with the product with no added maltodextrin to determine the effect of the carrier agent. The sorption isotherm and the critical moisture content of the product were established. Products with 1% maltodextrin had an intense colors but were not as free flowing as those with higher amounts of maltodextrin. Products with 3% matodextrin, on the other hand, had a low moisture content, high bulk density, and were free flowing but had less intense color. Product with 2% added maltodextrin were of suitable bulk density, had low moisture content and had dark colors. Product with no added maltodextrin had the most intense colors but the particles clumped because of a relatively high moisture content, thus, affecting bulk density and flowability. No significant difference existed between the colors of the reconstituted forms of the products with 2% maltodextrin and those without added carrier. Evaluating the sorption isotherm and critical moisture content, all the products proved to be hygroscopic but those with added maltodextrin had wider safety margins than those without added carrier, thus the former is expected to present less packaging problems.